Radiotherapy of Breast Cancer-Professional Guideline 1st Central-Eastern European Professional Consensus Statement on Breast Cancer - Csaba Polgár; Csaba Polgár; Zsuzsanna Kahán; Olivera Ivanov; Olivera Ivanov; Martin Chorváth; Andrea Ligačová; András Csejtei; Gabriella Gábor; László Landherr; László Mangel; Árpád Mayer; et al. (Frontiers Media S.A., 2022)
The international radiotherapy (RT) expert panel has revised and updated the RT guidelines that were accepted in 2020 at the 4th Hungarian Breast Cancer Consensus Conference, based on new scientific evidence. Radiotherapy after breast-conserving surgery (BCS) is indicated in ductal carcinoma in situ (stage 0), as RT decreases the risk of local recurrence (LR) by 50-60%. In early stage (stage I-II) invasive breast cancer RT remains a standard treatment following BCS. However, in elderly (≥70 years) patients with stage I, hormone receptor-positive tumour, hormonal therapy without RT can be considered. Hypofractionated whole breast irradiation (WBI) and for selected cases accelerated partial breast irradiation are validated treatment alternatives to conventional WBI administered for 5 weeks. Following mastectomy, RT significantly decreases the risk of LR and improves overall survival of patients who have 1 to 3 or ≥4 positive axillary lymph nodes. In selected cases of patients with 1 to 2 positive sentinel lymph nodes axillary dissection can be substituted with axillary RT. After neoadjuvant systemic treatment (NST) followed by BCS, WBI is mandatory, while after NST followed by mastectomy, locoregional RT should be given in cases of initial stage III-IV and ypN1 axillary status.